Efektivitas Pembelajaran Daring Terintegrasi di Era Pendidikan 4.0 - Yahya, Amri (Jurnal Teknologi dan Bisnis, 2021)
The Industrial Revolution 4.0 focuses on the use of the internet for everything or the Internet of Things (IoT). Internet of Things (IoT) creates space without distance. Simply use a smart phone, information from other parts of the world can be obtained quickly. Responding to this, the education system needs to be properly prepared so that the output of education is in accordance with the current era. The curriculum as part of education also needs to be adapted to the current developments. Education that is in accordance with the era of the industrial revolution 4.0 is education that does not only focus on the academic side, but education that is also able to accommodate advances in information and communication technology. The learning system using the blended learning method is the right choice of education for today’s children.